166 Maladaptive mechanisms for coping with the direct costs of injuries: foregoing medical care in Vietnam and Kenya. (5th May 2020) - Taber, Niloufer; Rao, Krishna; Pham, Cuong Viet; Mohd Yusoff, Mohd Fadhli; Bachani, Abdulgafoor M
Abstract : Statement of Purpose: Uninsured patients may attempt to cope with the costs of an injury through various financial and non-financial coping mechanisms. Certain coping mechanisms, such as reducing health care utilization, may minimize direct medical costs while increasing indirect costs. Methods/Approach: The Health, Economic and Long-term Social Impact of Injuries (HEALS) project was a hospital-based longitudinal study of patients conducted in four countries, including Vietnam and Kenya, in 2015–2016. Using baseline survey data, we compared differences in length of hospital stay by health insurance status using a multivariable linear regression, and conducted a multivariable logistic regression to evaluate the relationship between insurance and foregoing additional health care. Results: The sample included 1022 patients in Vietnam and 994 in Kenya. Of these, 56.2% and 68.8% lacked insurance and 21.5% and 3.7% left against medical advice in Vietnam and Kenya, respectively. In Vietnam, uninsured patients left 2.4 days earlier than those with insurance, controlling for injury severity and mechanism; patient demographics; pre-injury household poverty status and the patient's contribution to household income (β=-2.441, p <0.001). Compared to insured patients, uninsured patients in Vietnam had 2.3 times the odds of leaving against medical advice, controlling for the same set of variables. (OR= 2.327, p<0.001). In Kenya, those without insurance left on average 0.5 days earlier and had over 3 times the odds of leaving against medical advice, compared to insured patients, although neither estimate was statistically significant (β=-0.592, p=0.838 and OR=3.190, p=0.124). Conclusions: Patients without health insurance may be foregoing health care in order to avoid additional direct health care costs, and in the process increasing indirect costs if leaving against medical advice prolongs a period of disability. Significance and Contributions to Injury and Violence Prevention Science: Improving the breadth of health insurance can protect against both direct and indirect costs of injuries.